Inflammation and depression: an evolutionary framework for the role of physical activity and exercise - Carrera-Bastos, Pedro; Bottino, Breno; Stults-Kolehmainen, Matthew; Schuch, Felipe Barreto; Mata-Ordoñez, Fernando; Müller, Paulo T.; Blanco, José-Ramón; Boullosa, Daniel (Frontiers in Psychology, 2025)
Major Depressive Disorder (MDD) is a leading global health challenge, affecting nearly 5% of the population. Mounting evidence suggests that systemic low-grade chronic inflammation (SLGCI) plays a central role in the development and progression of MDD. This persistent inflammatory state results from unresolved immune activation and sustained exposure to modern lifestyle factors, such as sedentary behavior, poor diet, inadequate sleep, and psychological stress. Regular physical activity (PA), particularly exercise, has been shown to modulate inflammatory processes and improve depressive symptoms. This narrative review examines the complex interactions between inflammation and MDD, focusing on the role of PA and exercise in mitigating SLGCI and neuroinflammation. This is approached through an evolutionary lens, exploring how the mismatch between ancestral and modern activity levels may contribute to the rise of MDD. In addition, it highlights the potential risks of excessive exercise, including overtraining and its association with depressive symptoms. Finally, this work proposes a practical framework for optimizing PA and exercise as preventive and therapeutic tools for MDD by aligning modern PA patterns with ancestral behavioral norms.